The State of Food Insecurity: A comparative study of Sub-Saharan Africa and North Africa during the period 2020–2023 - Abdallah, Amina Serir; Djeddi, Ala Eddine (The International tax journal, 2025)
This study aims to determine the level of food insecurity in both Sub-Saharan Africa and North Africa by examining indicators such as undernourishment, the prevalence of food insecurity, and the affordability of a healthy diet, in addition to regional progress toward global nutrition targets. Through data analysis, the study found that Sub-Saharan Africa records high levels across all studied indicators, resulting in a severe degree of food insecurity. This is attributed to regional instability from wars and environmental changes. In contrast, North Africa's food insecurity levels fluctuated during the study period, influenced by the consequences of conflicts in neighboring countries, particularly illicit migration and its related effects.